ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN TEMPAT BERSALIN DI WILAYAH KERJA PUSKESMAS NAMOHALU ESIWA KABUPATEN NIAS UTARA TAHUN 2021 - Yanti Jernih Gea (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Based on the Basic Health Research (Riskesdas) in 2018, there were about 96 percent of pregnant women who had their health checked at the health facilities. However, only 79 percent gave birth at the puskesmas or hospital. According to a report by the World Health Organization (WHO), the direct cause of maternal death that occurs during and after childbirth. 75% of deaths are caused by bleeding, infection, or high blood pressure during pregnancy. Every woman has her own birth experience that can be shared with others. Most women in labor experience psychological changes in response to what is felt in the labor process. Maternal mortality as much as 70% occurs in the delivery process, this is related to the place where the delivery takes place. The purpose of this study was to analyze factors related to the choice of place of delivery in the working area of ​​the Namohalu Esiwa Public Health Center in 2021. This type of research used quantitative methods which were carried out by analytical survey with a cross sectional approach. The population in this study were all mothers who gave birth in January-March 2021 as many as 86 people with the sampling technique using total sampling so that the total sample was 86 people. Data analysis in this study used univariate analysis, bivariate and multivariate analysis with multiple logistic regression. The results of the study with the chi-square test obtained p-value on the knowledge variable of 0.001 <0.05, family support of 0.005 <0.05, education of 0.000 <0.05, distance of 0.000 <0.05, sources of information 0.40>0.05, employment 0.33>0.05, parity 0.84>0.05. The results of the multiple logistic regression test show that the distance variable has the largest PR value = 11.24. The conclusion of this study is that there is a relationship between knowledge, family support, education, and distance to the choice of place of delivery in the working area of ​​the Namohalu Esiwa Public Health Center in 2021. The most dominant variable related to the choice of place of delivery is distance. In front of the puskesmas officers, it is necessary to increase visits to mothers who will give birth and explain the dangers that will arise if giving birth at home.